Why Do Companies Create and How Do They Succeed with a Vendor-Led Open Source Foundation - Yenisen Yavuz, Elcin; Riehle, Dirk; Mehrotra, Ankita (Empirical Software Engineering, 2025)
Vendor-led open source foundations are open source foundations led by software vendors rather than individual developers or end-user organizations. Our research investigates why vendors create or join such foundations, and how these foundations succeed. We conducted exploratory single-case study research, with the LF Edge foundation as our case. We collected qualitative data in the form of interviews and text documents, and performed qualitative data analysis for building our theory. We identified 18 motives of vendors’ participation in vendor-led open source foundations regarding four aspects: revenue, competition, productivity and innovation, and reputation. To understand how vendor-led open source foundations succeed, we investigated good practices followed by LF Edge applied as preventions for potential problems or solutions for encountered problems. We determined 52 good practices in 20 different contexts, focusing on three dimensions: governance, efficiency and productivity, and sustainability.<br
Keywords: Open source foundations; open source projects; best practices; governance problems; coopetition; Linux Foundation; edge foundation